2020
DOI: 10.18502/ijph.v49i2.3104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated-Factors for Entamoeba gingivalis in Adolescents in Southeastern Iran by Culture and PCR, 2017

Abstract: Background: This study aimed to identify the prevalence and potential factors associated with Entamoeba gingivalis in adolescents in the city of Kerman, southeastern Iran, 2017. Methods: In this descriptive cross-sectional study, 315 adolescents (mean age; 15 yr) consisting of 189 males and 126 females were randomly selected. For each adolescent, two specimens were collected for culturing and examination by polymerase chain reaction (PCR). Univariate and multivariate logistic regression models were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
0
11
2
1
Order By: Relevance
“…The total percentage of E.gingivalis in the presented study was 46.25% this nearly similar to Al-Dulaimi et al, 2020 where found Entamoeba gingivalis in Babylon Province was (42.9 %). The results of the current study was much higher than what Rahdar found in his study that conducted in Iran, reported that only 16% of the patients were infected with E. gingivalis The study presented by Ghabanchi et al, 2010 found the prevalence of oral E.gingivalis in southern Iran was (66.7%), while Sharifi et al, 2020 found the prevalence of E. gingivalis was 11.7% also in Southeastern Iran, and this results that reported by Sharifi was much lower than what we found in our study.…”
Section: Isolation and Identification Of Entamoeba Gingivalis In Immu...contrasting
confidence: 69%
“…The total percentage of E.gingivalis in the presented study was 46.25% this nearly similar to Al-Dulaimi et al, 2020 where found Entamoeba gingivalis in Babylon Province was (42.9 %). The results of the current study was much higher than what Rahdar found in his study that conducted in Iran, reported that only 16% of the patients were infected with E. gingivalis The study presented by Ghabanchi et al, 2010 found the prevalence of oral E.gingivalis in southern Iran was (66.7%), while Sharifi et al, 2020 found the prevalence of E. gingivalis was 11.7% also in Southeastern Iran, and this results that reported by Sharifi was much lower than what we found in our study.…”
Section: Isolation and Identification Of Entamoeba Gingivalis In Immu...contrasting
confidence: 69%
“…Arene and colleagues observed a decrease in prevalence by age; thus, 22.9% of the 5–10 year-olds were colonized as opposed to only 5.7% of those aged 29 or more [ 20 ]. In the present study, the youngest participant was 17 years, so this cohort could not be used to confirm or challenge the observation by Arene et al A study from Iran found a significantly higher prevalence among men than among women [ 5 ]; however, other studies have failed to identify gender- or age-based differences [ 22 ].…”
Section: Discussionmentioning
confidence: 61%
“…These vast differences in positivity rates might reflect differences in diagnostic sensitivity among the methods used. In this study, we used DNA-based technology, which offers greater sensitivity than non-DNA-based methods, such as microscopy or culture, also in the case of E. gingivalis [ 5 , 11 ]. More data are needed, but the positivity rate observed in the present study could be a preliminary indication that E. gingivalis might be less common in the background population than in patients with periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations